COMPARISON OF ORAL HEALTH STATUS OF ADULTS IN RURAL URBAN COMMUNITIES IN LAGOS, NIGERIA - U.I. Ekowmenhenhen; K.O. Wright G.O. Uti, O.O. Sofola (UNILAG Journal of Medicine, Science and Technology, 2019)
Health inequalities and disparities are a global trend and could be found between rural and urban areas of both developed and developing countries. This study aimed to assess and compare health status of adults resident in rural and urban areas of Lagos State. A descriptive, comparative cross-sectional study conducted among 474 consenting adults aged 18-64 years in one rural and one urban local government area of Lagos State was done. Ethical approval was obtained from the Institutional Ethics Committee, Lagos University Teaching Hospital (LUTH). Data was obtained using an interviewer administered questionnaire. Descriptive statistics was used in data analysis whilst P values of <0.05 were considered significant.Majority of the respondents were within the age brackets of 20-39 years, with a mean age of 36.4+-36.1. Caries prevalence was 15.4% and 19.5%, mean DMFT was 0.72 and 0.62 in the rural and urban populations respectively. More respondents in the rural population (10%) (1.6389+1.05) had poorer oral hygiene than the urban population (6.5%). (Mean OHI 1.555+1.00).Urban respondents had greater need for periodontal treatment than rural respondents(2.3% vs 0.5%). There was a significant difference in the periodontal status and treatment need between rural and urban population. (P=0.041) But there was no significant difference in the oral hygiene status and dental caries experience between urban and rural populations. However, the oral hygiene status of the rural population was poorer. This study highlights the need for improved oral health promotion measures and preventive programs in rural and urban communities in Lagos state.